Microsatellite DNA markers to resolve population structure and hybridization of two closely related surgeonfish species, Acanthurus nigricans and Acanthurus leucosternon - Di Battista, Joseph; Feldheim, K.; Bowen, B. (Springer, 2011)
Ten polymorphic microsatellite loci were developed for sister surgeonfish species: the white cheek surgeonfish (Acanthurus nigricans) which occurs primarily in the Pacific Ocean, and the powder blue tang (Acanthurus leucosternon) in the Indian Ocean. All loci were scored for widely separated collections (A. nigricans, N = 30, French Polynesia; A. leucosternon, N = 27, Republic of Seychelles; hybrids, N = 17, Cocos/Keeling Island, eastern Indian Ocean). For A. nigricans, A. leucosternon, and hybrids, respectively, the mean number of alleles per locus is A = 17.80, A = 16.60, and A = 14.60, while observed heterozygosity ranges from H O = 0.78-1.00, H O = 0.74-0.96, and H O = 0.69-1.00. With the exception of locus Ahy54, all loci conformed to Hardy-Weinberg expectations, most loci were in linkage equilibrium, and there was little evidence for confounding null alleles. These markers will be used to resolve range-wide population structure and patterns of hybridization.